PENGARUH LATIHAN PEREGANGAN STATIS TERHADAP KELENTUKAN PADA ATLET PB. BHINEKA MAJAPAHIT - Ardita Pradayanti; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem with this research it still a lack of flexibility when they smash in Athlete PB. Bhineka Majapahit. Based on the researchers training provide Statis stretching. The study research to determine whether there is effect Statis Stretchings to the flexibility of Athlete PB. Bhineka Majapahit, so that when a jump smash to get the maximum smash. Forms of this research is the experimental treatment (Experimental), with a population of Athlete PB. Bhineka Majapahit, the data in this research is the entire population of 7 people. The instruments used in this research is to test Sit and Reach, which aims to measure the flexibility. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect Statis Stretchings to the flexibility. Based on the analysis of statistical data, there are an average Pree-test of 15,14 and an average post-test 21,15, then the data is normal with an increase of 6,01. Based on t test analysis produces Ttabel Thitung of 1,943 and 19,38, meaning Thitung> Ttabel. Thus, there Effect of Exercise Statis stretching on flexibility Athlete PB. Bhineka MajapahitKeywords : Statis stretching, the flexibility.